Further enhancement of Daerau-Levenshtein Distance algorithm applied in plagiarism detection - Marlon P. Davis and Miracle C. Padre. 4 0 16; 5 (2016)
u
Undergraduate Thesis: (BSCS major in Computer Science)- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2